THE IMPORTANCE OF INTERACTIVE TEACHING METHODS IN TEACHING CHEMISTRY IN HIGHER EDUCATION INSTITUTIONS (International journal of artificial intelligence, 2026)
This article discusses the use of modern teaching methods that can be applied to make the teaching of chemistry more engaging and effective for students of medical higher education institutions. It also highlights the relevance of new interactive teaching approaches in ensuring student participation and activity during lessons.